Impact pathways of a participatory local governance initiative in Uganda: A qualitative exploration - Van Campenhout, Bjorn; Bizimungu, Emmanuel; Smart, Jenny; Kabunga, Nassul S. (Routledge, 2018)
The baraza project, initiated in 2009, is a government-led initiative in Uganda that aims to increase the quality of public service delivery through the provision of information and involvement of beneficiaries in project monitoring by means of providing citizens with an advocacy forum. This article provides a qualitative assessment of the self-identified pathways through which barazas are thought to influence public service delivery, as expressed by participant stakeholders. It also explores motivating factors behind behavioural changes of stakeholders, hindrances to achieving positive outcomes, and opportunities for the implementation of future barazas.